New bio-nanocomposites based on iron oxides and polysaccharides applied to oxidation and alkylation reactions - Rodríguez-Padrón, Daily; Balu, Alina M.; Romero, Antonio A.; Luque, Rafael (Beilstein Journal of Organic Chemistry, 2017)
Polysaccharides from natural sources and iron precursors were applied to develop new bio-nanocomposites by mechanochemical milling processes. The proposed methodology was demonstrated to be advantageous in comparison with other protocols for the synthesis of iron oxide based nanostructures. Additionally, mechanochemistry has enormous potential from an environmental point-of-view since it is able to reduce solvent issues in chemical syntheses. The catalytic activity of the obtained nanocatalysts was investigated in both the oxidation of benzyl alcohol to benzaldehyde and in the alkylation of toluene with benzyl chloride. The microwave-assisted oxidation of benzyl alcohol reached 45% conversion after 10 min. The conversion of the alkylation of toluene in both microwave-assisted and conventional heating methods was higher than 99% after 3 min and 30 min, respectively. The transformation of benzyl alcohol and toluene into valuable product in both the oxidation and alkylation reaction reveals a potential method for the valorization of lignocellulosic biomass.
Keywords: alkylation; benzyl alcohol; benzyl chloride; iron oxide; mechanochemistry; microwave-assisted oxidation; polysaccharide; toluene

(untitled) - White, R. J.; Luque, R.; Budarin, V. L.; Clark, J. H.; Macquarrie, D. J. (Chem. Soc. Rev., 2009)

(untitled) - Astruc, D.; Lu, F.; Aranzaes, J. R. (Angew. Chem., Int. Ed., 2005)

(untitled) - Grunes, J.; Zhu, J.; Somorjai, G. A. (Chem. Commun., 2003)

Green Chemistry: Theory and Practice - Anastas, P. T.; Warner, J. C. (Oxford University Press, 1998)

(untitled) - Xu, C.; De, S.; Balu, A. M.; Ojeda, M.; Luque, R. (Chem. Commun., 2015)

Nanoparticles and catalysis - Astruc, D. (John Wiley & Sons, 2008)

(untitled) - Polshettiwar, V.; Luque, R.; Fihri, A.; Zhu, H.; Bouhrara, M.; Basset, J.-M. (Chem. Rev., 2011)

(untitled) - Cai, D.; Mataraza, J. M.; Qin, Z. H.; Huang, Z.; Huang, J.; Chiles, T. C.; Carnahan, D.; Kempa, K.; Ren, Z. (Nat. Methods, 2005)

(untitled) - Hu, X.; Dong, S. (J. Mater. Chem., 2008)

(untitled) - Balu, A. M.; Pineda, A.; Yoshida, K.; Campelo, J. M.; Gai, P. L.; Luque, R.; Romero, A. A. (Chem. Commun., 2010)

(untitled) - Garcia-Olmo, A. J.; Yepez, A.; Balu, A. M.; Romero, A. A.; Li, Y.; Luque, R. (Catal. Sci. Technol., 2016)

(untitled) - Ouyang, W.; Kuna, E.; Yepez, A.; Balu, A. M.; Romero, A. A.; Colmenares, J. C.; Luque, R. (Nanomaterials, 2016)

(untitled) - Colmenares, J. C.; Ouyang, W.; Ojeda, M.; Kuna, E.; Chernyayeva, O.; Lisovytskiy, D.; De, S.; Luque, R.; Balu, A. M. (Appl. Catal., B: Environ., 2016)

(untitled) - Yepez, A.; De, S.; Climent, M. S.; Romero, A. A.; Luque, R. (Appl. Sci., 2015)

(untitled) - Juárez, R.; Parker, S. F.; Concepción, P.; Corma, A.; García, H. (Chem. Sci., 2010)

(untitled) - Navalon, S.; Martin, R.; Alvaro, M.; Garcia, H. (Angew. Chem., Int. Ed., 2010)

(untitled) - Mendes, D.; Garcia, H.; Silva, V. B.; Mendes, A.; Madeira, L. M. (Ind. Eng. Chem. Res., 2009)

(untitled) - Gonzalez-Arellano, C.; Luque, R.; Macquarrie, D. J. (Chem. Commun., 2009)

(untitled) - Budarin, V. L.; Clark, J. H.; Luque, R.; Macquarrie, D. J.; White, R. J. (Green Chem., 2008)

(untitled) - Gonzalez-Arellano, C.; Yoshida, K.; Luque, R.; Gai, P. L. (Green Chem., 2010)

(untitled) - Yepez, A.; Lam, F. L. Y.; Romero, A. A.; Kappe, C. O.; Luque, R. (ChemCatChem, 2015)

Nanochemistry: A chemical approach to nanomaterials - Ozin, G. A.; Arsenault, A.; Cademartiri, L. (Royal Society of Chemistry, 2009)

(untitled) - Tsuzuki, T.; McCormick, P. G. (J. Mater. Sci., 2004)

(untitled) - Mei, K.-C.; Guo, Y.; Bai, J.; Costa, P. M.; Kafa, H.; Protti, A.; Hider, R. C.; Al-Jamal, K. T. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Ding, J.; Tsuzuki, T.; McCormick, P. G. (J. Mater. Sci., 1999)

(untitled) - Koch, C. C. (Nanostruct. Mater., 1993)

(untitled) - Ding, J.; Shi, Y.; Chen, L. F.; Deng, C. R.; Fuh, S. H.; Li, Y. (J. Magn. Magn. Mater., 2002)

(untitled) - Xu, C.; Ojeda, M.; Arancon, R. A. D.; Romero, A. A.; Domingo, J. L.; Gómez, M.; Blanco, J.; Luque, R. (ACS Sustainable Chem. Eng., 2015)

(untitled) - Herea, D. D.; Chiriac, H.; Lupu, N.; Grigoras, M.; Stoian, G.; Stoica, B. A.; Petreus, T. (Appl. Surf. Sci., 2015)

(untitled) - Rodriguez-Padrón, D.; Puente-Santiago, A. R.; Balu, A. M.; Romero, A. A.; Luque, R. (Chem. Commun., 2017)

(untitled) - Rodríguez-Padrón, D.; Puente-Santiago, A. R.; Caballero, A.; Benítez, A.; Balu, A. M.; Romero, A. A.; Luque, R. (J. Mater. Chem. A, 2017)

(untitled) - Huebsch, N.; Mooney, D. J. (Nature, 2009)

(untitled) - Salgueiriño-Maceira, V.; Correa-Duarte, M. A. (Adv. Mater., 2007)

(untitled) - Zheng, Y.; Monty, J.; Linhardt, R. J. (Carbohydr. Res., 2015)

(untitled) - Majewski, P.; Thierry, B. (Crit. Rev. Solid State Mater. Sci., 2007)

(untitled) - Tallury, P.; Payton, K.; Santra, S. (Nanomedicine, 2008)

(untitled) - Kim, J.; Piao, Y.; Hyeon, T. (Chem. Soc. Rev., 2009)

(untitled) - Pineda, A.; Balu, A. M.; Campelo, J. M.; Romero, A. A.; Carmona, D.; Balas, F.; Santamaria, J.; Luque, R. (ChemSusChem, 2011)

(untitled) - Matsumoto, T.; Ueno, M.; Wang, N.; Kobayashi, S. (Chem. – Asian J., 2008)

(untitled) - Dey, S. K.; Mukherjee, A. (Coord. Chem. Rev., 2016)

(untitled) - Rajabi, F.; Naresian, S.; Primo, A.; Luque, R. (Adv. Synth. Catal., 2011)

(untitled) - Yang, J.-C. E.; Yuan, B.; Cui, H.-J.; Wang, S.; Fu, M.-L. (Appl. Catal., B: Environ., 2017)

(untitled) - Huang, X.; Wang, X.; Wang, X.; Wang, X.; Tan, M.; Ding, W.; Lu, X. (J. Catal., 2013)

(untitled) - Rak, M. J.; Lerro, M.; Moores, A. (Chem. Commun., 2014)

(untitled) - Shi, F.; Tse, M. K.; Pohl, M.-M.; Brückner, A.; Zhang, S.; Beller, M. (Angew. Chem., Int. Ed., 2007)

(untitled) - Campelo, J. M.; Luna, D.; Luque, R.; Marinas, J. M.; Romero, A. A. (ChemSusChem, 2009)

(untitled) - Wilson, K.; Adams, D. J.; Rothenberg, G.; Clark, J. H. (J. Mol. Catal. A, 2000)

Speciality chemicals - Bastock, T. W.; Clark, J. H. (Elsevier Applied Science, 1991)

(untitled) - Pineda, A.; Balu, A. M.; Campelo, J. M.; Luque, R.; Romero, A. A.; Serrano-Ruiz, J. C. (Catal. Today, 2012)

(untitled) - Gracia, M. J.; Losada, E.; Luque, R.; Campelo, J. M.; Luna, D.; Marinas, J. M.; Romero, A. A. (Appl. Catal., A, 2008)

(untitled) - Ojeda, M.; Balu, A. M.; Barrón, V.; Pineda, A.; Coleto, Á. G.; Romero, A. A.; Luque, R. (J. Mater. Chem. A, 2014)

(untitled) - Bourlinos, A. B.; Simopoulos, A.; Boukos, N.; Petridis, D. (J. Phys. Chem. B, 2001)

Adsorption, Surface Area and Porosity - Gregg, S. J.; Sing, K. S. W. (Academic Press Inc., 1982)

(untitled) - Luque, R.; Campelo, J. M.; Luna, D.; Marinas, J. M.; Romero, A. A. (Microporous Mesoporous Mater., 2005)